A dynamic diffusion model for managing customer's expectation and satisfaction - Yeon, Seung-jun; Park, Sang-hyun; Kim, Sang-wook (Technological forecasting & social change, 2006)
The paper aims at answering the generic question on how suppliers make the suitable and well-timed decisions in diffusing new technology effectively to adopters. Three major attempts are made for the study: First, investigating the entire process of the adoption and diffusion of technology innovation with reasonably well-accepted models in each areas. Second, proposing an integrated model by concatenating in structured manner the three prominent models for the management of technology innovation such as diffusion model, adoption model, and customer satisfaction model. Third, exploring the dynamic mechanism underlying outward behaviors of the integrated model proposed in the study which depicts the causal relationships that influence technology adoption and diffusion behaviors. An exploration of the dynamic mechanism underlying outward behaviors of the integrated model is presented in the study by introducing the system dynamics simulation technique. These attempts made for the study and the results perhaps allow both researchers and practitioners to gain insight into the causal factors influencing customers' adoption decision making processes and thereby into the potential diffusion patterns resulting from those adoption processes.